Cross-country Spillovers of Renewable Energy Promotion - The Case of Germany - Mirjam Kosch; Jan Abrell (ZBW - Leibniz Information Centre for Economics, 2021)
Electricity generation based on renewable energy (RE) sources such as wind and solar replace the most expensive generators in the market, and thus induce a decrease in wholesale electricity prices. This so-called merit-order effect stimulates an increase in net-exports. Consequently, prices in neighboring countries are also likely to decrease. This cross-border merit-order effect causes opposing effects on consumers and producers: Generators' profits decline, while consumers benefit from decreasing prices and an increase in the consumer surplus. This implies that unilateral RE promotion, which is usually paid for by the consumers within the country itself, impact neighboring electricity markets. We estimate the cross-border merit-effect for German RE using hourly data on electricity generation, demand and wholesale prices for the period from 2015 to 2018. We find that German RE decreased electricity prices in surrounding countries by up to 10e/MWh or 23%, and can thus have a significant impact on their consumer and producer rents
Keywords: H23; 330; Renewable promotion; Electricity prices; Merit-order effect; Cross-border impacts